The Effect of Designed Exercise Program on Fatigue in Women with Breast Cancer Receiving Chemotherapy - M Aghabarari; F Ahmadi; H AghaAlinejad; E Mohammadi; E Hajizadeh (Tehran University of Medical Sciences, 2008)
Background: Fatigue identified as the most prevalent, disturbing and disabling symptom that has profound impact on quality of life in patients with breast cancer receiving chemotherapy. In these patients, unnecessary bed rest and prolonged sedentariness can potentially contribute significantly to the development of fatigue, so this study was carried out to investigate and determine the effect of designed exercise program on fatigue in women with breast cancer receiving chemotherapy.  Methods: This research was a quasi-experimental study with control and experimental groups carried out in cancer institute center of Tehran Imam Khomeini Hospital in 2006. The Piper Fatigue Scale used in order to measure subjective fatigue in behavioral, affective, sensory and cognitive dimensions before and after intervention. The intervention consisted of a designed exercise program at home 20 to 30 minutes every day, 3 to 5 days per week for 9 weeks (3 chemotherapy cycles). The control group during the study did not use any intervention except routine procedures. Results: Data analysis showed that the posttest mean of fatigue in four dimensions (Behavioral, Affective, Sensory, and Cognitive) in the experimental group was lower than the control group. Conclusion: According to the results, the designed exercise program was effective in reducing fatigue in women with breast cancer receiving chemotherapy. Therefore, it can be used as an effective approach for reducing fatigue in cancer patients, and improving the patient's quality of life.